PERLINDUNGAN HUKUM TERHADAP PIHAK PEMILIK SERTIPIKAT ASLI ATAS DITERBITKANNYA SERTIPIKAT PENGGANTI SECARA MELAWAN HUKUM - Victoria Suryana; Jur. Udin Silalahi (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2024)
The purpose of issuing a replacement certificate is to replace damaged land title certificates caused by accidental damage due to natural disasters or damage due to aging of the paper or tearing of the certificate due to the carelessness of the holder, which makes the certificate unusable. However, the issuance of a replacement certificate due to unlawful actions by the party claiming to be the land owner, creates a land dispute which results in losses for the original land owner. The problem in this research is how is the legal protection for the owner of the original certificate from the unlawful issuance of a replacement certificate? The results of the research show that the legal protection of the owner of the original certificate for the unlawful issuance of a replacement certificate is divided into 2 (two), namely, first, preventive legal protection through the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency of the Republic of Indonesia Number 21 of 2020 concerning Handling and Settlement of Land Cases through amicable settlement between land rights holders and the local Land Office, so that when administrative defects are discovered, the issuance of a replacement certificate can be cancelled. The second legal protection is carried out repressively through a lawsuit to annul the decision of the Head of the Land Office to the State Administrative Court and a lawsuit for an unlawful act to the District Court.